2020 AND THE REMOTE TEACHING PANDEMIC - Fortunato, Ivan [UNESP] (Unesp-faculdade Ciencias & Letras, 2021)
This text is a reflection on the context of remote emergency education experienced in the year 2020, due to the social isolation caused by the pandemic of the covid-19. This is an essay on the educational context caused by the pandemic that unfolds in two parts: (a.) The identification of false premises about education evidenced by the emergency situation and (b.) A mixture of bitterness and nostalgia provoked by the circumstances. In the end, there is the hope of a renewed world, of healthy agglomerations and face-to-face education with the end of this terrible pandemic.
Keywords: Pandemic; Remote teaching; Education